(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2012)
The will is one of the most consistent focuses of much of Husserl’s work beginning with the Logische Untersuchungen and continuing through his reflections in the 1930s. Any phenomenology of experience must account for the fact that every moment of our lives is marked by tension of will. Such a study, therefore, combines many important and interrelated issues, such as the problematic relationship between the voluntary and the involuntary sphere of the ego’s life. Over the history of the phenomenological movement, Husserl was not the only one to dedicate so much attention to the phenomenon of will. In addition to outlining Husserl’s phenomenology, this paper explores the phenomenological analyses of Alexander Pfänder and Moritz Geiger. In the wake of the traditional philosophical concept of the will, Pfänder considers the will as a dimension of pure activity and self-determination, whose peculiar trait is the so-called geistiger Schlag. Instead, Geiger points out the complexity of the voluntary dimension and advances the paradoxical hypothesis of the existence of a non-experienced will. Husserl moves deeper into this latter direction when he highlights the overall dimension of the will, which permeates the entire life of the ego even in the form of the Willenpassivität.